The role of regional and local incentives on the location of foreign firms in Portugal - Ribeiro, J. Cadima (1999)
Foreign direct investment is an issue of paramount importance in the Portuguese economy from the eighties onwards, especially ever since Portugal became an European Community member state. Nevertheless, little emphasis has been put on the role of the local and regional incentives (for example, financial incentives) to launch business and investment throughout the Portuguese territory. This paper seeks to shed light upon the above issue. Information has been gathered through interviews. Thirty seven foreign firms have been randomly selected from a representative sample. The results will be shown in this paper.